Are glyphosate or glyphosate-based herbicides linked to metabolic dysfunction-associated steatotic liver disease (MASLD)? The weight of current evidence - Riechelmann-Casarin, Luana [UNESP]; Valente, Leticia Cardoso [UNESP]; Otton, Rosemari; Barbisan, Luís Fernando [UNESP]; Romualdo, Guilherme Ribeiro [UNESP] (Elsevier, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) affects around 30 % of the world's population, increasing its prevalence by 50 % in the last three decades. MASLD pathogenesis is considered multiaxial, involving disturbances in the liver, adipose tissue (AT), and gut microbiome. In parallel with MASLD increasing trends, the total herbicide use has nearly tripled over the last three decades. Glyphosate (GLY) is the most used herbicide worldwide (825 mi kg/year). The intensive use of GLY-based herbicides (GBH) - largely driven by the adoption of glyphosate-tolerant genetically modified crops over the past two decades - has led to environmental (soil and water) and food contamination, resulting in continuous human exposure. Emerging (pre)clinical data highlights the significant implications of this herbicide on MASLD, marking a critical research area. Thus, this narrative review paper aimed at gathering and evaluating all epidemiological and (pre)clinical data on the implications of GLY or GBH on MASLD outcomes. Our work encompassed literature published between 2008-2025. Human urinary GLY levels are associated with different MASLD outcomes (steatosis risk, advanced fibrosis, increased transaminases) and comorbidities (higher risk for metabolic syndrome, diabetes, obesity and cardiovascular diseases) (6 studies). In vitro data indicate that GBH/GLY cause oxidative stress, genomic instability, apoptosis, and membrane disruption in hepatocytes, while promoting apoptosis and lipid peroxidation in (pre)adipocytes and cytokine production in monocytes (15 studies). In rodent studies (21 studies), GLY/GBH - in doses based on human exposure/toxicological limits - induces inflammatory and oxidative responses in the liver and AT, while causing dysbiosis and metabolic alterations in the gut microbiome axis. In the light of populational-, cell- and animal-based evidence, GLY/GBH disturbs key axis of MASLD pathogenesis and is hypothesized to be associated with its clinical outcomes.